Narrative Review on Dental Porcelain and Ceramics: A New Classification (Asian Journal of Pharmaceutics (AJP), 2025)
In recent years, there has been a surge in the development and introduction of various ceramic materials inrestorative dentistry. It has become increasingly evident that there is growing interest in ceramic materials indentistry. These materials are preferred over traditional ones because of their superior esthetic qualities and abilityto meet patients’ demands for improved appearance. The advent of computerized systems for producing dentalrestorations and the development of novel microstructures for ceramic materials have significantly changed theclinical workflow for dentists and technicians. This has led to new treatment options being available to patients.This review includes a comprehensive search of literature and clinical survival papers on ceramic materials indentistry published between the 1960s and 2024. Major databases, such as PubMed, Scopus, and Google Scholar,were used for the investigation. The aim is to summarize the literature and update clinicians’ knowledge aboutdental ceramics and their clinical applications. This review suggests a new classification of dental ceramics basedon their composition, considering commercially available materials. A summary of each category’s mechanicalproperties and clinical applications is also provided. The purpose is to simplify the understanding of dentalceramics and assist clinicians in choosing appropriate materials for their patients.